Variability in Ultrasound Backscatter Induced by Trabecular Microstructure Deterioration in Cancellous Bone. (29th January 2018) - Chou, Xingxing; Xu, Feng; Li, Ying; Liu, Chengcheng; Ta, Dean; Le, Lawrence H.
Abstract : To determine the relationship between the ultrasonic backscatter parameters and trabecular microstructural variations in cancellous bone, three erosion procedures were performed to simulate various changes in the cancellous bone microstructure. The finite difference time domain (FDTD) method was used to simulate the backscatter signal in cancellous bone. Ultrasonic backscatter properties were derived as functions of the porosity when the ultrasound incident directions were perpendicular and parallel to the major trabeculae direction (MTD), respectively. The variability in the apparent backscatter coefficient (ABC) and apparent integrated backscatter (AIB) due to the trabecular microstructure was revealed. Significant negative correlations between the backscatter parameters (ABC and AIB) and the porosity of the cancellous bone were observed. The simulations showed that the ABC and AIB were influenced by the direction of the trabecular microstructural variations. The linear regressions between the ultrasonic backscatter parameters (ABC and AIB) and the porosity showed significantly different slopes for three erosion procedures when they are ultrasonically perpendicular (for ABC, −1.22 dB, −0.98 dB, and −0.46 dB; for AIB, −0.74 dB, −0.69 dB, and −0.25 dB) and parallel (for ABC, −1.87 dB, −0.69 dB, and −0.51 dB; for AIB, −0.9 dB, −0.5 dB, and −0.34 dB) to the MTD. This paper investigated the relationship between ultrasonic backscatter and cancellous bone microstructure deterioration and indicated that the ultrasonic backscatter could be affected by cancellous bone microstructure deterioration direction.